Prosedur Pengambilan Keputusan Di Lembaga Pendidikan Tinggi Di Era Revolusi Industri 4.0 - Biqrotul Azizah; Imam Syafi’i (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
This article aims to describe the process of making and effective methods for the dissemination of decision results in the Industrial Revolution 4.0 era. This research uses library research taken from scientific journals and relevant literature. The results showed that the most effective decision making process was a combination of top-down and bottomup with formal decision-making mechanisms or decisions. Decision making formally involves leaders and subordinates and adjusted to the output of the meeting. The dominant dissemination mechanism is traditional dissemination through meetings and through social networks. The implications of the results of this study indicate that the formal process of decision making through public meetings or limited meetings is still the choice of the decision making process so that this traditional model provides space for all elements involved to participate and provide constructive advice for effective decision making.